The Association between Temperament, Chronotype, Depressive Symptoms, and Disease Activity among Patients with Inflammatory Bowel Disease—A Cross-Sectional Pilot Study - Łukasz Mokros; Danuta Domżał-Magrowska; Tadeusz Pietras; Kasper Sipowicz; Renata Talar-Wojnarowska (Life, 2021)
The psychological aspect may play an important role in ulcerative colitis (UC) and Crohn’s disease (CD). The aims of this study were to explore the differences between patients with UC and CD regarding chronotype, temperament and depression, and to assess the psychological factors mentioned as predictors of disease activity. In total, n = 37 patients with UC and n = 47 patients with CD were included in the study. They underwent a clinical assessment, including the Mayo score or Crohn Disease Activity Index (CDAI), and completed questionnaires: a sociodemographic survey, Formal Characteristics of Behavior–Temperament Inventory (FCB-TI), Chronotype Questionnaire (CQ), and the Beck Depression Index II (BDI). The Sensory Sensitivity score was higher among patients with CD than UC (p = 0.04). The emotional reactivity and endurance scores were higher among women than men with CD (p = 0.028 and p = 0.012 respectively). CQ Morningness–Eveningness (ME) correlated with Endurance (p = 0.041), Emotional Reactivity (p = 0.016), and Activity (p = 0.004). ME correlated with Rhythmicity among CD patients (p = 0.002). The Mayo score was predicted by Perseverance. The CDAI score was predicted by the BDI score. The pattern of the relationship between chronotype and temperament may differentiate patients with UC and CD. Personal disposition may play a role in the clinical assessment of patients with IBD.